Studies on genetic variability and selection criteria in F3 generation of a cross fenugreek (Trigonella foenum-graecum L.) - L Singhania, J Mahey, R S Raje, D (Journal of Spices and Aromatic Crops, 2003)
Thirty F3 families of the cross UM - 305 x Um - 117 in fenugreek were evaluated for seed yield and other component characters. Substantial amount of genetic variability was observed at inter as well as intra-family levels for all the observed characters. Plant height and number of pods per plant, haing true positive association with seed yield per plant, were mainly under the control of additive gene action and thus, direct selection for these characters would be effective for the improvement of seed yield per plant. Genetic variability at the intra-family level could be exploited by further selection for plant height and number of pods per plant. Superior families with respect to high mean performance for seed yield and its components were also identified. these families will be useful in developing high yielding fenugreek genotypes.